Comparison Between Two Routes of Misoprostol for First Trimester Pregnancy Termination - ديوب ميسون; حسن سحر; طربيه هبة (Latakia University Journal -Medical Sciences Series, 2020)
Background: Early pregnancy loss is common accuring in 10% of all clinically recognized pregnancies the present study aimed to compare the efficacy of Misoprostol in first trimester abortion through two sublingual and vaginal routes of administration. Methods: This randomized clinical trial was conducted in Tishreen Hospital on 60 consecutive women. The patients were hospitalized and then randomly assigned to receive sublingual Misoprostol (400µg) or vaginal Misoprostol (400µg) placed in posterior fornix every 4h up to 5 doses. Results: There was a significant difference in complete evacuation rates between the sublingual misoprostol and the vaginal misoprostol groups 70% vs. 43.3%, p = 0.04). Side effects were seen more in the sublingual group compared to vaginal group specially diarrhea (p=0.02) and abdominal pain (p=0.0001). Conclusion: The use of Misoprostol in vaginal route results in more abortion completeness as well as lower Side effects rate compared to sublingual prescription of the drug.